Distributional and taxonomic notes on the crab spider genus Talaus Simon, 1886 with description of a new species (Araneae: Thomisidae) - Benjamin, Suresh P. (Zootaxa, 2020)
Taxonomic notes on the crab spider genus Talaus Simon, 1886 are provided. One new species, T. beccarii sp. nov. is described. Further four species are redescribed: T. nanus Thorell, 1890, T. triangulifer Simon, 1886, T. oblitus O. Pickard-Cambridge, 1899 and T. opportunus (O. Pickard-Cambridge, 1873). Talaus now contains 13 species.